2013
DOI: 10.1227/neu.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Dynamic Rod Segments for Achieving Transitional Stiffness With Lumbosacral Fusion

Abstract: The effect of the dynamic rod segment on the kinematics of the transition level was less pronounced than that of a fully rigid construct in vitro with this particular rod system. This experimental model detected no biomechanical alterations at adjacent intact levels with hybrid or rigid systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Most multisegmental studies involved one [ 32 , 33 , 35 , 36 , 38 , 40 , 42 , 44 49 , 51 56 , 59 , 65 , 66 , 68 70 , 72 , 74 , 75 ] (60.9%) or two [ 34 , 37 , 39 , 41 , 43 , 50 , 60 , 62 , 64 , 67 , 71 , 76 ] (26.1%) operative level(s) in their testing sample. Moreover, the L3-L4 and the L4-L5 were the most frequent operative levels used in multisegmental investigations (58.7%) that included one or more spinal segment as their operative level(s).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most multisegmental studies involved one [ 32 , 33 , 35 , 36 , 38 , 40 , 42 , 44 49 , 51 56 , 59 , 65 , 66 , 68 70 , 72 , 74 , 75 ] (60.9%) or two [ 34 , 37 , 39 , 41 , 43 , 50 , 60 , 62 , 64 , 67 , 71 , 76 ] (26.1%) operative level(s) in their testing sample. Moreover, the L3-L4 and the L4-L5 were the most frequent operative levels used in multisegmental investigations (58.7%) that included one or more spinal segment as their operative level(s).…”
Section: Resultsmentioning
confidence: 99%
“…A follower compressive preload of 400 N during FE motion was used in thirteen (13) [ 44 50 , 56 , 61 , 65 , 69 , 70 , 76 ] of the nineteen (19) multisegmental publications reporting the use of some preload in at least one of their flexion-extension (FE) tests. There were four (4) publications [ 52 , 53 , 59 , 60 ] that mentioned the performance of an additional test where a 400 N follower compressive load was applied through a notched belt looped oriented midsagitally over the specimen using a compression-flexion apparatus, which were not included in Table 2 under the preload classification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, in a study of a device with similar design characteristics to the PDS device used in the current study, Lazaro et al found significantly greater LB and AT ROM in the flexible rod compared to a titanium rod. 22 However, it is critical to note that this study investigated both implants as stand-alone devices with no interbody spacer, constituting a motion-preserving construct which is a commonly referenced configuration for this class of devices. 23 25 Since the current study was designed to elucidate differences in fixation and load sharing of the two devices used in an adjunct-to-fusion model, no evaluation of the devices as stand-alone fixation was conducted.…”
Section: Discussionmentioning
confidence: 99%